Effect of the addition of inhibitors of kirinyuh leaf (Chromolaena Odorata) in methanol extract on corrosion rate of ASTM 36 steel - Fauzi Widyawati; Syamsul Hidayat; Syamsul Bahtiar; Musbihin Musbihin (Jurnal Pijar Mipa, 2022)
Kirinyuh leaves (Chromolaena Odorata) contain alkaloids, saponins, flavonoids, phenols, and tannins with the potential as a natural inhibitor that can be used to inhibit the rate of corrosion. Kirinyuh leaf extract inhibitors were added at various concentrations of 100 ppm, 200 ppm, 300 ppm, 400 ppm, and 500 ppm, which were sprayed onto the sample surface before being soaked for seven days. Calculation of the corrosion rate using the method of weight loss (weight loss). The results showed that kirinyuh leaf extract effectively inhibited the corrosion rate. The smallest corrosion rate value was found in the sample with the addition of 400 ppm inhibitor concentration, which was 2.053 ppm. Meanwhile, an efficiency inhibitor was also found in the same concentration of inhibitor that is equal to 87%.